Transnational Flows and Permissive Polities - Sur, Malini; Kalir, Barak (Amsterdam University Press, 2012)
This book is a collection of ethnographies of transnational migration and border crossings in Asia. Interdisciplinary in scope, it addresses issues of mobility and Diaspora from various vantage points. Unique to this volume is an emphasis of studying globalisation from below, privileging the narratives and views of -people on the move˜ or the transnational underclass and their sense of belonging to places and communities. The collection is further distinguished by its focus on the sources of authority and the social configurations that are created in the intersections between legality and illegality across Asia. Though previous studies on transnational flows have deconstructed the notion of nation-states as having fixed political boundaries, and have engaged in spaces beyond the nation-states, seldom has an entire region, Asia, been privileged in one integrated volume. We emphasize hitherto marginalized debates that have significant policy relevance. Other than a serious academic interest from lecturers and students, we are confident that book will be of significant interest for development practitioners and NGOs.